2022
DOI: 10.1002/ajhb.23726
|View full text |Cite
|
Sign up to set email alerts
|

A critical biocultural approach to early growth in the United States

Abstract: Objectives A critical biocultural anthropology seeks to link perspectives from social theory and ethnography to human biology. In the United States (U.S.), multiple forms of structural inequalities affect early growth, including racism and poverty. The goal of this paper is to test the effects of social inequalities on birth weight and later height in the U.S. National Health and Nutrition Survey (NHANES), and to contextualize potential pathways of embodiment that link social structure and biology. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Prior studies showed that low birth weight was related to racism [2], being part of a racial/ethnic minority [2][3][4][5][6][7], poverty [2,3], food insecurity and a lack of health insurance coverage [7], having a single mother, the mother's age and education [3,5], maternal smoking [4,5,7], parenting [8], stressful work [6], and being a female infant [3]. Furthermore, two prior studies reported that low birth weight was negatively associated with children's growth in their early childhood [9,10]. Since these risk factors probably continue during infants' growth, it is thus crucial to identify risk and protective factors in low-birth-weight children's health in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies showed that low birth weight was related to racism [2], being part of a racial/ethnic minority [2][3][4][5][6][7], poverty [2,3], food insecurity and a lack of health insurance coverage [7], having a single mother, the mother's age and education [3,5], maternal smoking [4,5,7], parenting [8], stressful work [6], and being a female infant [3]. Furthermore, two prior studies reported that low birth weight was negatively associated with children's growth in their early childhood [9,10]. Since these risk factors probably continue during infants' growth, it is thus crucial to identify risk and protective factors in low-birth-weight children's health in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Research in human biology and the social sciences show strong links between both FI and poverty with a range of poor outcomes, such as: inadequate nutritional intake (Smith & Richards, 2008), adiposity (Moffat et al, 2005), flatter diurnal cortisol slopes (Heissel et al, 2017), and poor growth in infancy (Miller, 2022). These results broadly confirm that structural socioeconomic factors, such as poverty or housing instability, are crucial to determining disease outcomes and mortality risk.…”
Section: Introductionmentioning
confidence: 99%